Comparative Analysis of Architectural Aspects at Pasar Kampung Melayu and Pasar Komplek Mutiara Garuda, Kabupaten Tangerang - Shafira Ardhani Shafira Ardhani; Freta Oktarina Freta Oktarina (Program Studi Arsitektur, Fakultas Teknik, Universitas Riau, 2026)
Pasar Kampung Melayu is the only market managed by the Government of Kabupaten Tangerang. Pasar Kampung Melayu is located in a very strategic location, which is in the center of Kampung Melayu Subdistrict, Kabupaten Tangerang. However, this does not rule out the possibility that this market is not operating optimally because of the emergence of a competing market, namely the Pasar Komplek Mutiara Garuda. The existence of the Pasar Komplek Mutiara Garuda is one of the attractions for traders and also the community to seek economic opportunities, thus making the performance of the Pasar Kampung Melayu decline. The purpose of this research is to see the comparison between the two markets in architectural technical terms, especially in terms of accessibility and market facilities. The research method used is qualitative with data collection by conducting observations, interviews, and literature studies. The results of this study will ultimately describe the comparison between the two markets in architectural aspects, especially in terms of accessibility and market facilities that affect the performance of Pasar Kampung Melayu